Peran Brand Love Memediasi Pengaruh Service Quality terhadap Electronic Word of Mouth (E-Wom) Gojek di Kota Denpasar - Ni Komang Diah Ayumi; I G. A. Kt. Giantari (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the mediating role of brand love in the relationship between service quality and electronic word of mouth (e-WOM), with a focus on Gojek users in Denpasar City. The background of this research is grounded in the increasing competition within the digital transportation service industry, where service quality serves as a key determinant in fostering customers’ emotional attachment to the brand (brand love), which in turn encourages consumers to share their experiences through electronic word of mouth. A total of 115 respondents participated in this study, selected using a non-probability sampling method with purposive sampling technique. Data were collected through questionnaires, with 30 percent distributed online via Google Forms and 70 percent offline. The findings reveal that: (1) service quality has a positive and significant effect on e-WOM, (2) service quality has a positive and significant effect on brand love, (3) brand love has a positive and significant effect on e-WOM, and (4) brand love mediates the effect of service quality on e-WOM. The theoretical implications of this study reinforce prior research findings through the lens of the Consumer Behavior Model. Practically, the results highlight the importance of consistently improving Gojek’s service quality to nurture brand love, which ultimately motivates customers to voluntarily share their experiences via digital media in the form of e-WOM.